Rubble women: The long-term effects of postwar reconstruction on female labor market outcomes - Mevlude Akbulut-Yuksel; Melanie Khamis; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2011)
During World War II, more than one-half million tons of bombs were dropped in aerial raids on German cities, destroying about forty percent of the total housing stock nationwide. With a large fraction of the male population gone, the reconstruction process had mainly fallen on women in postwar Germany. This paper provides causal evidence on long-term legacies of postwar reconstruction and mandatory employment on women's labor market outcomes. We combine a unique dataset on city-level destruction in Germany caused by the Allied Air Forces bombing during WWII with individual survey data from the German Microcensus. Using difference-in-difference and instrumental-variable strategies, we find that postwar mandatory employment reduced female labor force participation and hours worked in the long-run. However, our results show that participating in postwar reconstruction efforts increased the female presence in medium-skill and female-dominated occupations. These results survive after accounting for labor supply side factors such as wealth and savings loss during WWII, war relief payments and change in the composition of population and labor demand side factors such as female share in industry, construction, service and public sectors.
urn:nbn:de:101:1-2012010913684
Keywords: I21; I12; J24; N34; 330; postwar reconstruction; female labor force participation; occupational choice; Kriegsschaden; Weibliche Arbeitskräfte; Erwerbstätigkeit; Berufswahl; Schätzung; Deutschland